Original paperSynthesis of α-collagen fragments and research of their influence on the degree of hydration of a model of epidermis - Łubkowska, Beata; Grobelna, Beata; Maćkiewicz, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction: In recent years the interest into areas of science, such as cosmetology, dermatology, pharmacology or aesthetic medicine has increased significantly. Scientists are more frequently looking for ingredients that affect the skin’s condition and slow down the aging process. Practically every year, the scientists discover a number of new chemical substances (both natural and synthetic) that can be potentially used to manufacture cosmetics. Aim : To evaluate the influence of selected peptides derived from α-collagen fragments on the degree of hydration of a model of epidermis isolated from a pig. Material and methods: The synthesis of selected cosmetic oligopeptides were performed manually, on the solid medium, using procedure of SPPS (solid phase peptide synthesis). Following components: aqua, carbomer, glycerine, phenonip, D-panthenol, dimethicone and triethanolamine were used to prepare a reference hydrogel masks. Both the number of components and the composition of hydrogels have been developed individually for the purposes of this research. For this study the skin from a domestic pig was used. The degree of the skin hydration was measured with the SKINTEST plus camera, which uses the latest semiconductor technology. Results : During the study the absorption of hydrogels with peptides was faster than that of the reference hydrogel mask. The combination of hydrophilic properties of the peptide with hydrophobic properties of Palm enabled receiving an amphiphilic structure. Such molecules are considered to be able to penetrate the corneum barrier with the greatest ease. Conclusions : The results showed that the modified compounds have contributed to water retention in the cells, thereby increasing the degree of hydration of the biological material.